Trans Dermal Testosterone Compared to Intramuscular Testosterone for Young Males with Delayed Puberty: A PRISMA Guided Systematic Review - Jabari M (International Journal of General Medicine, 2023)
Mosleh Jabari Department of Endocrinology, College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi ArabiaCorrespondence: Mosleh Jabari, Department of Endocrinology, College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia, Email dr.mosleh.jabari@gmail.comBackground: Challenges in selecting the right formulation of testosterone (TE) for young males with delayed puberty (DP) arise from the fact that there is limited evidence based guidelines in recommending the most efficient and safe formulation of TE.Objective: To evaluate the existing evidence and systematically review the interventional effects of transdermal TE to other modes of TE administration for the treatment of DP among young and adolescent males.Methods: All types of methodologies published in English were searched from the data sources including MEDLINE, Embase, Cochrane Reviews, Web of Science, AMED and Scopus from 2015 till 2022. Boolean operators with keywords “types of TE”, “modes of TE administration”, “DP”, “transdermal TE”, “constitutional delay of growth and puberty, (CDGP)” “adolescent boys” and “hypogonadism” to optimize the search results. The main outcomes of concern were optimal serum TE level, body mass index, height velocity, testicular volume, pubertal stage (Tanner), The secondary outcomes included in this study were adverse events and patient satisfaction.Results: After screening 126 articles, 39 full texts were reviewed. Only five studies could be included after careful screening and rigid quality assessments. Most studies were at high or unclear risk of bias with short duration and follow up periods. Only one study was a clinical trial covering all the outcomes of interests.Conclusion: This study points out the favorable effects of transdermal TE treatment for DP in boys, while the existence of the vast gap in research needs to be acknowledged. Despite the utmost demand in an appropriate TE treatment for young males with DP, scarce efforts and trials are being undertaken to provide clear clinical guidance of treatment. Quality of life, cardiac events, metabolic parameters, coagulation profiles are important aspects of the treatment are overlooked and under evaluated in most studies.Systematic Review Registration: PROSPERO CRD 42022369699.Keywords: delayed puberty, transdermal testosterone, testosterone treatment, hypogonadism, constitutional delay of growth, DP, TT